2020
DOI: 10.1111/sltb.12653
|View full text |Cite
|
Sign up to set email alerts
|

Associations among state‐level physical distancing measures and suicidal thoughts and behaviors among U.S. adults during the early COVID‐19 pandemic

Abstract: Purpose The purpose of this study was to identify leading sources of stress, describe rates of mental health outcomes, and examine their associations among U.S. adults during the first months of the COVID‐19 pandemic. Method In a cross‐sectional, general population survey conducted from March 18 to April 4, 2020, U.S. adults (n=10,625) were recruited through Qualtrics Panels using quota sampling methods. Results Life stressors, probable depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 14 publications
2
55
0
2
Order By: Relevance
“…Online Supplementary Table S1 provides an overview of all included studies. Thirteen studies were conducted in Europe (Bojanowska, Kaczmarek, Kościelniak, & Urbańska, 2020;Daly & Robinson, 2020;Jackson, Garnett, Shahab, Oldham, & Brown, 2020;Kwong et al, 2020;Niedzwiedz et al, 2020; Ozamiz-Etxebarria, Dosil-Santamaria, Picaza-Gorrochategui, & Idoiaga-Mondragon, 2020; Pierce et al, 2020;Recchi et al, 2020;Schützwohl & Mergel, 2020;Shanahan et al, 2020;Stevenson, Wakefield, Drury, & Felsner, 2020;Zacher & Rudolph, 2020), six in Asia (Guo, Feng, Wang, & van Ijzendoorn, 2020;Lei et al, 2020;Li, Cao, Leung, & Mak, 2020;Liu et al, 2020;Wang & Zhao, 2020;Xin et al, 2020), five in North America (Bryan, Bryan, & Baker, 2020;Gratz et al, 2020;Luchetti et al, 2020;Tull et al, 2020;Zimmermann, Bledsoe, & Papa, 2020), and one in Oceania (Sibley et al, 2020). The majority of the included studies (n = 16) were peer-reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Online Supplementary Table S1 provides an overview of all included studies. Thirteen studies were conducted in Europe (Bojanowska, Kaczmarek, Kościelniak, & Urbańska, 2020;Daly & Robinson, 2020;Jackson, Garnett, Shahab, Oldham, & Brown, 2020;Kwong et al, 2020;Niedzwiedz et al, 2020; Ozamiz-Etxebarria, Dosil-Santamaria, Picaza-Gorrochategui, & Idoiaga-Mondragon, 2020; Pierce et al, 2020;Recchi et al, 2020;Schützwohl & Mergel, 2020;Shanahan et al, 2020;Stevenson, Wakefield, Drury, & Felsner, 2020;Zacher & Rudolph, 2020), six in Asia (Guo, Feng, Wang, & van Ijzendoorn, 2020;Lei et al, 2020;Li, Cao, Leung, & Mak, 2020;Liu et al, 2020;Wang & Zhao, 2020;Xin et al, 2020), five in North America (Bryan, Bryan, & Baker, 2020;Gratz et al, 2020;Luchetti et al, 2020;Tull et al, 2020;Zimmermann, Bledsoe, & Papa, 2020), and one in Oceania (Sibley et al, 2020). The majority of the included studies (n = 16) were peer-reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…19 Recently, some studies have reported suicide cases triggered by the adverse effects of mass quarantine, and staying at home could increase suicide risk through thwarted belongingness. [20][21][22][23] It is noteworthy that physical distancing measures themselves were shown not associated with elevated incidence of suicidal behaviors, 24 which indicates that mass quarantine related suicide was probably because of social disconnection. Therefore, keeping socially connected through online platform or apps may help prevent suicide during the pandemic of COVID-19.…”
mentioning
confidence: 99%
“…Therefore, keeping socially connected through online platform or apps may help prevent suicide during the pandemic of COVID-19. 24 Second, economic recession induced by COVID-19 itself and anti-epidemic measures has commonly occurred. Worsening economic conditions and increasement of unemployment was another pandemic related factor that has been proven associated with a higher risk of suicide.…”
mentioning
confidence: 99%
“…Web-based survey platforms using sampling methods could avoid such selection bias. Two published surveys [ 6 , 11 ] used Qualtrics Panels, a web-based survey platform that uses quota sampling methods to identify participants who meet a given study’s eligibility criteria, with a target to recruit a sample that is demographically similar to the 2010 United States census distributions for age, sex, and race or ethnicity (with a ±10% variation). Qualtrics Panels maintains a database of several million US residents who have volunteered to participate in periodic survey-based research.…”
Section: Discussionmentioning
confidence: 99%